Evolving a Model in Islamic Economy: Industrial Development - Said, Mohamed Mohamed Tolba; Umachandran, Krishnan (2018)
Economic growth in the Islamic economy depends on the demand and manufacturers competitive capability to compete. The factors such as vicissitude of changes in production volumes, labor productivity, employment, export and import volumes affect the competitiveness of the organization’s position in the Islamic economy. Capital and technological reserves are obligatory to balance the enormous productivity fissure between developing and developed countries symbolizing the world economy. Need to exports is required as a nourishment to fill the productivity gap. The structure of economic openness depends on the level of free-trade, therefore advancement should entail an identical momentum of long-term investment to the absorption of substantial segments of all business activities. Hence this paper drives a weave to connect various aspects of management resources. The enlargement of international commerce requires a critical flexibility in the setting of tariff rates by developing countries and a steady rise in the sum of customers that can participate in business with decreasing debt-line. To a developing country, the benefits when it opens its borders to foreign capital, improves FDIs and leads in generation of positive employment impacting both job creation for suppliers, retailers and tertiary employment effecting additional generation of incomes aggregating on the demand. Islamic economization aids economic growth and therefore poverty reduction, hence the ecosystem should encompass complementary economic factors and policies.